Tribus urbanas: estudio de caso sobre la construcción del lazo social en el adolescente desde una orientación psicoanalítica (2018)
The following research is part of the need to understand how urban scenarios, discursive practices, social imaginary, the linkage and/or interaction of adolescents with a particular urban tribe, enable and contribute not only to the Foundation of the identity in the university adolescents, subject of study but also to the ways to establish bonds and to build a social bond with the other members of the tribe. The methodology of research took as a reference the qualitative paradigm that aims to investigate, interpret and understand the social realities, mentalities and subjectivities of the subjects of study. From this analytical and interpretative reading, an approximation was generated to the understanding and abstraction of meaning and meaning of the identity building of the group of students participating in this research. The focus of the research is historical hermeneutic, because through it it is possible to interpret and understand what are the internal motivations of human action and in what context it is exerted, thus allowing a better understanding and from which it was sought Delve into the reflective analysis of your daily work in the different areas where adolescents are mobilizing sample research. As to the scope of this research it is comprehensive, because it seeks to understand how urban tribes influence the construction of the social bond. With regard to the techniques of information collection is working through the technical case studies, stories of life and semi-structured interviews, applied to a group of students of the educational community of the University of the Coast, in the city of Barranquilla.